Influence of dietary fatty acid, vegetable, and vitamin intake on etheno-DNA adducts in white blood cells of healthy female volunteers: a pilot study - Keßler, Tina; Nair, Jagadeesan; Becker, Nikolaus; Bartsch, Helmut (Cancer epidemiology, biomarkers & prevention, 2001)
Etheno-DNA adducts such as 1,N6-ethenodeoxyadenosine (εdA) and N2,3-ethenodeoxycytidine (εdC) are formed as result of oxidative stress and lipid peroxidation via reactive alkenals (J. Nair et al., Mutat. Res., 424:59-69, 1999). High ϖ-6 polyunsaturated fatty acid intake markedly increased levels of WBCs in female volunteers on a controlled diet (J. Nair et al., Cancer Epidemiol. Biomark. Prev., 6:591-601, 1997). In healthy female volunteers we investigated possible correlations between dietary fatty acid intake (by questionnaire), concentration of linoleic acid (LA) and oleic acid (OA) in serum (n = 34), and etheno-DNA adduct levels in WBC (n = 42). Two groups of samples were selected according to dietary intake >15 g (group A) or <5 g (group B) LA/day. Serum samples were analyzed for free OA and LA by gas chromatography-mass spectroscopy and WBC-DNA for εdA and εdC adducts by immunoaffinity 32P postlabeling. On a group level, serum LA and OA concentrations were higher in group A than group B, whereas the LA/OA ratios were similar. The mean εdA and εdC levels did not significantly differ in groups A and B, but a third of the individuals had more than twice the mean adduct levels than the rest. Correlation analyses revealed a significant inverse correlation for εdA in WBC-DNA and vegetable or vitamin E consumption. We conclude that etheno-DNA adduct levels are not determined by LA intake alone but might depend on the ratio of ϖ-6 polyunsaturated fatty acid:other fatty acids and of antioxidants consumed in the diet. This pilot study also indicated a protective effect of dietary vitamin E and vegetables against miscoding, lipid peroxidation-induced DNA lesions.
Gesehen am 12.01.2001